2014
DOI: 10.1590/1982-43272459201404
|View full text |Cite
|
Sign up to set email alerts
|

The Positivity Dimension of Well-Being: Adaptation and Psychometric Evidence of a Measure1

Abstract: This research aimed to adapt the Positivity Scale (PS) to the Brazilian context, gathering evidence of validity and reliability. Two studies were performed. Study 1 was composed of 200 people from Paraíba, with a mean age of 23.4 years old (SD = 4.53), who answered the PS and demographic questions. Results pointed to a one-factor solution in this scale, which presented satisfactory reliability (α = .85). Study 2 gathered 290 undergraduate students with a mean age of 23.9 years old (SD = 7.60), who answered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
4
0
6
Order By: Relevance
“…Positivity scale. This instrument was developed by Caprara, Steca, Alessandri, Abela, and McWhinnie (2010), and adapted to the Brazilian context by Souza, Araújo, Gouveia, Coelho, and Gouveia (2014). It assesses the individuals' level of positivity, which is an important aspect of well-being.…”
Section: Instrumentsmentioning
confidence: 99%
“…Positivity scale. This instrument was developed by Caprara, Steca, Alessandri, Abela, and McWhinnie (2010), and adapted to the Brazilian context by Souza, Araújo, Gouveia, Coelho, and Gouveia (2014). It assesses the individuals' level of positivity, which is an important aspect of well-being.…”
Section: Instrumentsmentioning
confidence: 99%
“…It was developed by Caprara et al (2012) and has been adapted to the Brazil context by Souza, Araújo, R. Gouveia, Coelho, and V. Gouveia (2014). It consists of eight items [e.g., I generally feel confident in myself; At times, the future seems unclear to me.]…”
Section: Instrumentsmentioning
confidence: 99%
“…They have also found significant positive correlations between positivity and optimism, self-esteem, life-satisfaction, and negative correlations with depression. Souza, Araújo, Gouveia, Coelho, and Gouveia et al (2014) in their adaptation study tested psychometric properties of the P Scale in a Brazilian sample. The unidimensional structure of the scale by this study was once more confirmed.…”
Section: Discussionmentioning
confidence: 99%